Efek Media Slide dan Media Sosial terhadap Pengetahuan HIV/AIDS dan VCT (Voluntary Counseling and Testing) pada Pekerja PT. X di Kabupaten Tabalong - Astuti, Henni Widia; Rezeki Sudarmin, Ria; Hairuddin, Hairuddin; Meiliani Yulis, Dian; Herman, Sriyana (NHM PRESS, 2024)
This study aims to analyze the effectiveness of health promotion media, namely slide media and social media (animated videos), in improving workers' knowledge and interest in HIV/AIDS and Voluntary Counseling and Testing (VCT) at PT. X, Tabalong Regency, South Kalimantan. The study utilized a quasi-experimental design with a two-group pre-posttest method, involving 360 respondents. Group A received counseling using slide media, while Group B was educated through animated videos shared via WhatsApp. The results showed a significant increase in knowledge in both groups, with the slide media group demonstrating higher effectiveness compared to the social media group (p < 0.001). However, interest in VCT did not show a significant relationship with increased knowledge in either group (p > 0.05). Slide media proved to be more effective than social media in enhancing workers' knowledge of HIV/AIDS. These findings highlight the importance of using appropriate health promotion media to educate workers about health issues.